The International Responsibility for Protection of Victims from Armed Conflicts (Study of Iraq Case) - Khaleel Ibrahim, Imad (Opción, 2019)
It has adopted a wide range of international legal norms that recognize human rights and fundamental freedoms, both at the level of general rules, international human rights law and international humanitarian law, and in view of the various violations of these rights resulting from the wars or conflicts that have raged - - The international community, whether interna- tional or non-international, and the resulting serious violations of the rules of international law in general and international humanitarian law in particu- lar, have been supplemented by these rules and texts with other legal proce- dures to provide international institutional mechanisms to implement the rules As well as the development and strengthening of the international liability regime that arises when the obligation to implement or violate it is violated. In light of the prevalence of the state of war as a sign of sovereignty at that time, the rules of international humanitarian law were gradually adopted with a view to codifying its customary rules and thus the norms of general international law which subjected the issue of resorting to war and the use of force to an international organization with many images: The Hague Conventions of 1899 and 1907 and the Covenant of the League of Nations, as well as its prohibition under the Brian Kellock Charter in Paris, until it was expressly prohibited under Article 2 (4) of the Charter of the United Nations. There is no doubt that the first of the problems faced by States in the application of the rules of international humanitarian law is the importance of finding a balance between military necessity and humanitarian concerns. The use of force will lead to the violation of these humanitarian norms, thereby refuting the principle of necessity. Therefore, there are fundamental principles relating to the right to redress and redress for victims of armed conflicts, including (missing persons and their families) at the international level in general, and with regard to Iraq in particular, in accordance with the scope of the multilateral international responsibility towards individuals, States, international organizations and security companies, There are also multiple mechanisms to implement this responsibility in accordance with national and international legal norms. Opening words: international law, international humanitarian law, national law, international responsibility